The Problem of Silt in Relation to Irrigation and River Projects and the Role of Forests - Sinha, R. L. (Indian Forester, 1957)
This dissertation after dealing in brief with the importance of our various multi-purpose irrigation and river projects, describes the mechanism of silt production, and the nature of the silt problem. It gives statistics in support of, and possible remedial measures to solve, the sediment problem. The principles of afforestation and soil-conservation works to be followed, alongwith special mention of the role of forests, in the management of watershed and catchemnt areas, have been discussed. Re-afforestation and practice of various soil-conservation methods are the cheapest measures to solve the sediment problem at its very source in the hilly catchment areas.